2014
DOI: 10.1177/2150135113507292
|View full text |Cite
|
Sign up to set email alerts
|

Does Single Ventricle Physiology Affect Survival of Children Requiring Extracorporeal Membrane Oxygenation Support Following Cardiac Surgery?

Abstract: The ECMO is valuable in patients with SV however results depend on anatomy, procedure, and support indication. Persistent markers of poor perfusion, end-organ injury, and prolonged ECMO duration are associated with mortality. Those factors could be modified by early ECMO application before organ damage, meticulous homeostasis to ensure adequate perfusion, early diagnosis, and reoperation on residual lesions to expedite weaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 23 publications
5
72
1
1
Order By: Relevance
“…Odds of survival were found to be significantly lower in patients who required support beyond 96 hours in the study by Jolley et al (1). This is consistent with multiple single-center reports that have identified an inflection point for survival after 4 days of support (2,(5)(6)(7)(8).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Odds of survival were found to be significantly lower in patients who required support beyond 96 hours in the study by Jolley et al (1). This is consistent with multiple single-center reports that have identified an inflection point for survival after 4 days of support (2,(5)(6)(7)(8).…”
supporting
confidence: 92%
“…Although several centers (6)(7)(8) failed to identify CPR duration as a predictor of ECPR survival, the median duration of CPR was greater than 30 minutes in these studies, and the observed difference in CPR duration between survivors and nonsurvivors was generally small (< 5 min). Taken together, these findings suggest improved survival for children who receive ECLS within 30 minutes of cardiac arrest (5,12).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Despite this finding, a survival benefit of ECPR was observed even after prolonged (>60 min) CPR, with 18% ECPR vs. 0% conventional CPR patients in this category surviving to hospital discharge. Currently available data do not support the use of duration of pre-ECLS resuscitation as a contraindication to ECPR but suggest that the shorter duration (≤30 min) of ECLS resuscitation is associated with better survival (24,30).…”
Section: Duration Of Pre-ecpr Resuscitationmentioning
confidence: 99%
“…[10][11][12][13][14] Although initial experience with ECMO was largely related to patients with two ventricle cardiac malformations, the application of ECMO in SV patients gradually increased, and many studies reported hospital survival that was comparable to that in patients with two ventricle malformations. 6,7,15,16 Approximately, 10% to 20% of neonates undergoing the Norwood operation require postoperative ECMO support with reported hospital survival ranging between 30% and 60%. [3][4][5][17][18][19][20][21] Nonetheless, few studies suggested that those patients continue to be prone to high attrition risk following hospital discharge, with only a few patients reaching the Fontan final stage palliation or having late survival.…”
Section: Introductionmentioning
confidence: 99%